On polysemiotic interactions, visual paratexts and image-specific translation in comics: The case of Rodolfo Santullo and Matías Bergara's Dengue. Issue 2 (1st November 2019) - Fraser, Benjamin
AbstractThe practice of translation in comics has received relatively little scholarly attention. This article focuses on translation decisions as they are carried out in the medium-specific interplay of words and images that constitutes the comics text. Using the case of Dengue (Santullo and Bergara) in both its Spanish (2012) and English (2015) versions, analysis explores how polysemiotic interactions, visual paratexts and image-specific translation inform the resulting graphic novel. Discussion centres on how the English version effects a significant thematic shift that is consistent across the cover art, frontmatter, chapter title pages, and individual panel rewordings.